The Resignation Reporting News of The President’s Staff Via Online Media: A Norman Fairclough Critical Discourse Analysis - Rina Husnaini Febriyanti; Hanna Sundari (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
The current research analyses the critical discourse on news broadcasting of president staff resigning Adamas Belva Syah Devara (ABSD) in online news mass media. Those are Detik.com, Kompas.com CnnIndonesia.com, CNBCIndonesia.com, Nasionaltempo.com, Kumparannews.com, Liputan6.com, VOAIndonesia.com, MediaIndonesia.com, and Republika.co.id. The method used was qualitative descriptive. Then data were analyzed using a content analysis procedure guided by the CDA theory of Norman Fairclough that involved text analysis, discourse practice, and sociocultural practice. The result displayed 1) text analysis exposed that eight online media broadcasted the news based on open letter made by ABSD and two rest media need openness and transparency of ABSD’s polemics, 2) discourse practice described the eight of them agree with following ABSD’s statement while two others tried to express other issues surrounding the main issue of staff resignation, and 3) sociocultural practice revealed the emergence of a polemic in the conflicts of interest Skill Academy as a part of ABSD’s Ruangguru that becomes the partner of Pre-employment card. The implication of this study is necessary for CDA toward news content broadcasted on the online media, and tight filtration is a must. Besides, the written and displayed news should be on the fact toward the reader. Additionally, how the media should act as a source of public information should be neutral and impartial. Hence, the presented informed news is objectively and accurately displayed